(untitled) (Quaderni di Gargnano, 2022)
This essay investigates the religious dimension of Dante’s Vita nuova through its biblical sources. It aims to demonstrate how the young Dante constructs his book of self-renewal by following a pattern of alternating emphasis on his poetic career (from its beginnings to the height of his Florentine fame), and simultaneously on his spiritual experience. The work thus dramatizes the first stages of a salvation history that will reach fulfillment only in the Commedia. Hypostases of the figure of Love are fundamental to Dante-author’s depiction of these early stages of Dante-character’s story. No mere courtly personification, Dante’s complex portrayal of Love invites the Vita nova’s readers to recognize the interpretive challenges of a work with two possible layers of meaning, literal and anagogical. As he adapts the book’s lyrics to their new context, Dante resemanticizes the classical and courtly image of Love so that, as the narrative unfolds, we understand increasingly clearly that Love corresponds to Beatrice, and to the unique religious sentiment that she inspires. Il saggio indaga la dimensione religiosa del libello dantesco attraverso le sue fonti bibliche, cercando di mostrare come il giovane Dante costruisca il libro del suo rinnovamento seguendo il ritmo alternato della carriera poetica, dagli esordi fino alla notorietà fiorentina, e nel contempo della propria vicenda spirituale, drammatizzando nell’opera i primi momenti di una storia della salvezza che troverà compimento soltanto nella Commedia. Nel delineare le prime fasi di questa storia per il Dante personaggio, il Dante autore ha creato diverse ipostasi della complessa figura di Amore, figura che non deve essere appiattita sulla tradizione cortese e la cui comprensione aiuterà a formulare criticamente il problema dei due sensi attraverso cui si può leggere la Vita nova, il senso letterale e il suo sovrasenso anagogico. La figura d’Amore della tradizione classica e cortese è al centro di un processo di risemantizzazione dovuto al necessario adattamento delle liriche al nuovo contesto. Sin dall’inizio dell’opera, e via via più chiaramente nello snodarsi della narrazione, si comprende che Amore corrisponde a Beatrice e al nuovissimo sentimento religioso da lei ispirato.